Решите уравнение: 1)(x+9)^2-x(x+8)=1 2) (х-11)^=(х-7)(х-9) 3) (х-4)(х+4)-(х+6)^2=-16 4) (1-3х)^2-х(9х-2)=2

Решите уравнение: 1)(x+9)^2-x(x+8)=1 2) (х-11)^=(х-7)(х-9) 3) (х-4)(х+4)-(х+6)^2=-16 4) (1-3х)^2-х(9х-2)=2
Гость
Ответ(ы) на вопрос:
Гость
1) (x+9)^2-x(x+8)=1 x^2+18x+81-x^2-8x=1 18x+81-8x=1 10x=-80 x=-8 2) не понятно, какая там степень 3)(x-4)(x+4)-(x+6)^2=-16 x^2+4x-4x-16-(x^2+12x+36)=-16 x^2-16-x^2-12x-36=-16 -12x=36 x=-3 4) (1-3x)^2-x(9x-2)=2 1-6x+9x^2-9x^2+2x=2 -4x=1 x=-1/4
Не нашли ответ?
Ответить на вопрос
Похожие вопросы